Gender diversity, investor sentiment and IPO underpricing - Chan, Yih Sen (2019)
This study first examines the level of initial public offering (IPO) underpricing in Malaysia. Then analyse the IPO underpricing by using prospectus disclosure, gender diversity and investor sentiment variables. Lastly is the comparison between the IPO underpricing in Main and ACE market. This research acquires the data of 129 IPOs that listed on the Bursa Malaysia between January 2010 and June 2018. The result declares the average underpricing in Malaysia is 12.6%, while Main market and ACE market have an average of 8.67% and 20.2%. Firm size and profitability are showing a negatively significant result. The finding argues the firm size has reduced the ex-ante uncertainty and profitability are providing a quality signal to investors. By analysing the gender diversity variables, female CEO is significantly reducing the level of underpricing in Malaysia. The reason behind that is investors interpret female CEO as good corporate governance also women are more conservative and risk-avoidance which help to reduce the ex-ante uncertainty. On the other hands, investor behaviour has played an important role in explaining IPO underpricing in Malaysia. The finding presents the higher oversubscription rate and higher trading volume have caused a higher initial return, which argues that investors are strongly influenced by the others investor decision and investor sentiment has caused the shares price to deviate from its intrinsic value. When a further investigation into the Main market and ACE market, the result states the gender diversity and investor sentiment are the significant influences of IPO underpricing in Malaysia. Female CEO confirms the significant impact on the Malaysia IPO market, which showing a significant result in the overall sample, Main and ACE market. Besides, the underpricing in Main market is affected by oversubscription rate while the first-day trading volume is influenced initial return in ACE market. Therefore, it concludes gender diversity and investor sentiment are the significant impacts on the level of underpricing in Malaysia.